Editorial: Dilemmas of Modern Economy and Business - Jelena Stankevičienė; Marek Szarucki (Entrepreneurial Business and Economics Review)
Various dilemmas concerning modern economy and business have been in the focus of scientific discussion in recent years (Klich, 2013; Renko & Knezevic, 2013; Szarucki, 2013; Agrawal & Gugnani, 2014; Pardhasaradhi & Grace, 2015). In modern economy, not only researches but corporations face complex economic and business dilemmas in their daily routine. The Joint Research Centre of the European Commission addresses key economic challenges by stimulating innovations, sustainability policies, social and environmental responsibilities. These challenges require the mobilization of significant resources by science, innovation and regional policy makers and scientific communities across Europe (EUA, 2014). Broader scientific discussions are crucial for the success of the Europe 2020 strategy for smart, sustainable and inclusive growth.